Il Paesaggio un tema transdisciplinare - Elvira Petroncelli (Didaskein, 2019)
According to the European Landscape Convention, signed in Florence on 20 October 2000, the landscape is the outcome of the relationship between local communities and their territories, as a result of the social culture that collective behaviors substantiate to build identities. Aware that everyone has an active role in shaping landscapes, the volume addresses some key aspects of the theme with a specialized but transversal approach. It is paired by the reflections of schoolteachers, who have implemented initiatives with students of Campania schools aimed at bringing them closer to their territories and to make them aware of the active role they have in its transformation. The origin of this symbiosis is the Training Project "Landscape from everyone - Landscape for everyone. Training and education for the awareness of new generations" developed and implemented by the local group of the University of Naples Federico II of the UNISCAPE (European Network of Universities for the Implementation of the European Landscape Convention) Association and the Regional School Office of Campania.